Frailty and falls among adult patients undergoing chronic hemodialysis: a prospective cohort study - McAdams-DeMarco, Mara A (BioMed Central, 2013)
BACKGROUND: Patients undergoing hemodialysis are at high risk of falls, with subsequent complications including fractures, loss of independence, hospitalization, and institutionalization. Factors associated with falls are poorly understood in this population. We hypothesized that insights derived from studies of the elderly might apply to adults of all ages undergoing hemodialysis; we focused on frailty, a phenotype of physiological decline strongly associated with falls in the elderly. METHODS: In this prospective, longitudinal study of 95 patients undergoing hemodialysis (1/2009-3/2010), the association of frailty with future falls was explored using adjusted Poisson regression. Frailty was classified using the criteria established by Fried et al., as a combination of five components: shrinking, weakness, exhaustion, low activity, and slowed walking speed. RESULTS: Over a median 6.7-month period of longitudinal follow-up, 28.3% of study participants (25.9% of those under 65, 29.3% of those 65 and older) experienced a fall. After adjusting for age, sex, race, comorbidity, disability, number of medications, marital status, and education, frailty independently predicted a 3.09-fold (95% CI: 1.38-6.90, P=0.006) higher number of falls. This relationship between frailty and falls did not differ for younger and older adults (P=0.57). CONCLUSIONS: Frailty, a validated construct in the elderly, was a strong and independent predictor of falls in adults undergoing hemodialysis, regardless of age. Our results may aid in identifying frail hemodialysis patients who could be targeted for multidimensional fall prevention strategies.